AMINOHYDROLASES ACTING ON ADENINE, ADENOSINE AND THEIR DERIVATIVES - Pospisilova, Hana; Frebort, Ivo (Biomedical papers, 2007)
Background: Adenine and adenosine-acting aminohydrolases are important groups of enzymes responsible for the metabolic salvage of purine compounds. Several subclasses of these enzymes have been described and given current knowledge of the full genome sequences of many organisms, it is possible to identify genes encoding these enzymes and group them according to their primary structure.Methods and Results: This article is a short overview of the enzymes classified as adenine and adenosine deaminase. It summarises knowledge of their occurrence, genetic basis and their catalytic and structural properties.Conclusions: These enzymes are constitutive components of purine metabolism and their impairment may cause serious medical disorders. In humans, adenosine deaminase deficiency is linked to severe combined immunodeficiency and as such the enzyme has been approved for the first gene therapy trial. The role of these enzymes in plants is unclear, since the activity was has not been detected in extracts and putative genes have not been yet cloned and analyzed. A literature search and amino acid identity comparison show that Ascomycetes contain only adenine deaminase, but not adenosine deaminase, despite the fact that corresponding genes are annotated in databases as the adenosine cleaving enzymes because they share the same conserved domain.
Keywords: Adenine deaminase/Adenase/Adenosine deaminase/Aminohydrolase/Gene organization/Protein structure